Ultrathin mesoporous Co3O4 nanosheets on Ni foam for high-performance supercapacitors. (1st March 2015) - Qiu, Kangwen; Lu, Yang; Cheng, Jinbing; Yan, Hailong; Hou, Xiaoyi; Zhang, Deyang; Lu, Min; Liu, Xianming; Luo, Yongsong
Graphical abstract: Abstract: Ultrathin Co3 O4 nanosheets with a mesoporous structure and a large surface area are hydrothermally grown on a three dimensional nickel foam. The ultrathin mesoporous Co3 O4 nanosheets are grown on Ni foam with robust adhesion, which endows fast ion and electron transport, large electroactive surface area, and excellent structural stability. Such unique nanoarchitecture exhibits remarkable electrochemical performance with high capacitance and desirable cycle life. When evaluate as an electrode material for supercapacitors, the Co3 O4 nanosheets electrode is able to deliver high specific capacitance of 2194 F g −1 at a current density of 1 A g −1 in 1 M KOH aqueous solution. The electrode also exhibits excellent cycling stability by retaining 93.1% of the maximum capacitance after 5000 charge-discharge cycles. The fabrication strategy presented here is facile, cost-effective, and can offer a way for energy storage device applications.